Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock